2020
DOI: 10.3390/ijerph17165671
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Physical Fitness of Children and Adolescents: A Review of Large-Scale Epidemiological Studies Published after 2006

Abstract: Physical fitness (PF) of children and adolescents is an important resource for their future health. Population-based studies, however, rarely report secular changes of PF, although monitoring of these is crucial to deriving information for adequate interventions. This review aims to report trends in PF of children and adolescents. A literature search was conducted in PubMed in July 2019. Cohort studies published in English allowing statements to be made on trends in PF by comparing youth between the ages of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 49 publications
14
67
0
Order By: Relevance
“…The observation of a declining trend of flexibility in this study is consistent to previous studies conducted among similar age groups 12 , 21 , 23 , 32 , 36 , 47 . Flexibility performance is associated to body size (mainly to body-mass index), and since we observed a significant increase of body-mass index from 1999 to 2014, it is possible that such increase would correlate to a negative trend of flexibility 21 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The observation of a declining trend of flexibility in this study is consistent to previous studies conducted among similar age groups 12 , 21 , 23 , 32 , 36 , 47 . Flexibility performance is associated to body size (mainly to body-mass index), and since we observed a significant increase of body-mass index from 1999 to 2014, it is possible that such increase would correlate to a negative trend of flexibility 21 .…”
Section: Discussionsupporting
confidence: 93%
“…Of note, we observed that the level of cardiorespiratory fitness had declined from 1999 to 2014 by ≈ 22.0% for both sexes, which is similar to previous studies using 20-m shuttle run test as a proxy of cardiorespiratory fitness 16 . In general, a recent systematic review aiming to report trends in physical fitness has shown, that the declining trend in cardiorespiratory fitness is more obvious in studies with more time periods or longer follow-ups 36 , which has also been supported by large-scale epidemiological findings 18 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, physical fitness (PF) levels appears to be declining in this population [ 13 , 14 ]. Accordingly, childhood and adolescence is a critical period for the development of PF [ 15 ] and adolescence has been identified as one of the stages that may play a critical role in the development and persistence of obesity and related comorbidities into adulthood [ 16 ]. As the social environment for adolescents diversifies and they become more independent, the key influences on their eating practices begin to change [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, a longitudinal study showed a moderate to a highly significant correlation between health-related physical fitness components in childhood and those in adulthood (6). With the growing public health concern worldwide, there is an overall declining trend of physical fitness among children (7). Hence, the improvement and maintenance of physical fitness have become the main challenges for many researchers.…”
Section: Introductionmentioning
confidence: 99%